The Distinctive Challenges of Pervasive Games as Distributed Real-Time Applications - Benford, Steve (2006 Tenth IEEE International Symposium on Distributed Simulation and Real-Time Applications, 2006)
Pervasive games are an emerging form of distributed real-time application that extend computer gaming out into the real world. From the city streets to the remote wilderness, players with mobile computing devices move through the world, sensors capture information about their current context, including their location, and this is used to deliver a gaming experience that adapts to where they are, what they are doing, and even how they are feeling. Players becomes unchained from their consoles and experience a game that is interwoven with thereal world and that is potentially available at any place and any time. Pervasive Games raise significant new challenges for the designers of distributed real-time applications, many of which arise from the distinctive characteristics of the underlying fabric of sensing and wireless communications technologies that constitute the ubiquitous computing infrastructure. Drawing on a series of recent collaborations with artists to develop, tour and study pervasive games, I will articulate these distinctive design challenges, exploring issues such as support for location-based play, revealing the nature of the ubiquitous infrastructure to designers, and adapting long-term persistent games with patterns of daily life.